Fish or steel? New evidence on the environment-economy trade-off in developing Vietnam. (November 2021) - Nguyen, Quynh; Malesky, Edmund
Highlights: Conventional thinking on the trade-off between economic growth and environmental protection provides an important but limited understanding of the way individuals in developing countries weigh development and environmental considerations; the environment is far more important to their calculus than previously understood. Unique public opinion data across three years (2017, 2018, 2019) with nationally representative samples of the Vietnamese population is used to model how environmental factors affect individuals' investment policy preferences when there is a potential trade-off. In all three years, a conjoint survey experiment identifies multi-dimensional policy preferences and provides shielding, so responsents can answer honestly. Citizens do not blindly prioritize economic goals over environmental quality. Their preferences are most strongly driven by the perceived potential environmental consequences of the investment. Specifically, the larger the potential environmental costs, the less likely respondents were to support the business' investment license application. While individuals are tolerant of some environmental damage in exchange for jobs or other economic benefits, there is a clear threshold beyond which people are unwilling to tolerate greater environmental costs regardless of the size of economic benefits. This preference for environmental quality remains consistent across different demographic groups and subnational locations. Abstract: Trade and investment have contributed to the improvement of living standards in developing countries, but have also put severe pressure on natural environments. How do citizens in low-income countries manage this trade-off between economic growth and environmental protection? Using a discrete choice experiment conducted as part of three large, face-to-face nationally representative surveys of Vetnamese citizens (N=>12, 500 respondents per wave), we find that prospective economic benefits increase public support for investment projects, whereas potential environmental harm resulting from investment decreases the public appetite for them. When economic and environmental factors are considered jointly, our results point to the existence of an environmental risk threshold. Environmental costs beyond that threshold lead citizens to reject investment projects, even when they generate considerable economic benefits. Our results challenge the theory that individuals in low-income countries prioritize development over environmental protection, and have implications for political leaders in designing their countries' future investment policies.